2012
DOI: 10.5392/ijoc.2012.8.3.012
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Acceptance and Resistance of Smart TVs

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Ko,Chang & Chu [3] distinguished between 21 functions for digital TV application services and found that apps like video-on-demand had the largest direct effect on the users' intention to adopt digital TV application services However, exactly what determines if users adopt and use such services is still an open question. A few authors already investigated factors that drive the adoption of smart TVs in general [1] [2]. Lee [1] identified six key constructs deduced from several innovation adoption models (e.g., technology acceptance model (TAM), diffusion of innovation theory (DIT)) such as perceived usefulness / perceived ease of use, and perceived risk.…”
Section: Literature Review Of Success Factors In Smart Tv (Applicatiomentioning
confidence: 99%
See 2 more Smart Citations
“…Ko,Chang & Chu [3] distinguished between 21 functions for digital TV application services and found that apps like video-on-demand had the largest direct effect on the users' intention to adopt digital TV application services However, exactly what determines if users adopt and use such services is still an open question. A few authors already investigated factors that drive the adoption of smart TVs in general [1] [2]. Lee [1] identified six key constructs deduced from several innovation adoption models (e.g., technology acceptance model (TAM), diffusion of innovation theory (DIT)) such as perceived usefulness / perceived ease of use, and perceived risk.…”
Section: Literature Review Of Success Factors In Smart Tv (Applicatiomentioning
confidence: 99%
“…A few authors already investigated factors that drive the adoption of smart TVs in general [1] [2]. Lee [1] identified six key constructs deduced from several innovation adoption models (e.g., technology acceptance model (TAM), diffusion of innovation theory (DIT)) such as perceived usefulness / perceived ease of use, and perceived risk. However, due to the abstract manner of such concepts it was difficult to derive insights for our specific use case.…”
Section: Literature Review Of Success Factors In Smart Tv (Applicatiomentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated consumer preferences in adopting smart TVs, but they simply analyzed the effects of particular functions and consumer characteristics in the adoption of smart TVs [11][12][13][14][15][16]. Prabhala and Ganapathy [14] analyzed consumer perceptions of smart TVs from the viewpoint of artificial intelligence, and Shin and Kim [15] investigated the effect of interactions between users and smart TVs on consumers' perceptions, attitudes, and willingness to use.…”
Section: Introductionmentioning
confidence: 99%
“…Prabhala and Ganapathy [14] analyzed consumer perceptions of smart TVs from the viewpoint of artificial intelligence, and Shin and Kim [15] investigated the effect of interactions between users and smart TVs on consumers' perceptions, attitudes, and willingness to use. Lee [13] introduced six main factors (perceived usefulness, perceived ease of use, etc.) that affect smart TV adoption using the technology acceptance model and diffusion of innovation theory.…”
Section: Introductionmentioning
confidence: 99%